Edukasi Manfaat Tablet Tambah Darah (Fe) dan Asam Folat pada Remaja Putri - Ari Sasanti, Dewi; Pradea Wulandari; Yuni Setia Ningsih; Anisa Secha Aulia (UNIVERSITAS NGUDI WALUYO, 2025)
The adolescent stage of life is marked by physical development, cognitive growth, and emotional well-being, laying the foundation for lifelong health and well-being. Although adolescence is considered a healthy time, many health issues are of concern, including mental health issues. Reports indicate that one in five adolescents experiences a mental health problem, most commonly depression or anxiety.This education aims to increase the understanding of young women about the importance of consuming iron (Fe) and folic acid tablets every month. This community service program was held at SMK Muhammadiyah 1 Balikpapan, and involved distributing educational booklets to 34 participants, followed by a question-and-answer session. Through education and counseling, the young women were given an understanding of the benefits, how to use them, and the importance of regularly consuming iron and folic acid tablets. The results of the community service demonstrated increased knowledge and awareness among young women about the importance of maintaining reproductive health and preventing anemia. Therefore, this service is expected to have a positive impact on the health of young women and reduce the risk of anemia in this group. ABSTRAK Tahap kehidupan remaja ditandai dengan perkembangan fisik, pertumbuhan kognitif dan emosional, meletakkan landasan bagi kesehatan dan kesejahteraan yang baik seumur hidup. Meskipun masa remaja dianggap sebagai masa yang sehat, banyak kesehatan masalah menjadi perhatian termasuk masalah kesehatan mental. Menurut laporan, satu dari lima remaja mengalami gangguan mental masalah kesehatan, paling sering depresi atau kecemasan. Edukasi ini bertujuan untuk meningkatkan pemahaman remaja putri pentingnya mengkonsumsi tablet tambah darah (Fe) dan asam folat setiap bulan nya. Pengabdian Masyarakat ini dilaksanakan di SMK Muhammadiyah 1 Balikpapan dengan edukasi melalui booklet yang di bagikan kepada 34 peserta dan dilanjutkan dengan sesi tanya jawab. Melalui edukasi dan penyuluhan, remaja putri diberikan pemahaman tentang manfaat, cara penggunaan, dan pentingnya konsumsi tablet Fe dan asam folat secara teratur. Hasil pengabdian menunjukkan peningkatan pengetahuan dan kesadaran remaja putri tentang pentingnya menjaga Kesehatan reproduksi dan mencegah anemia. Dengan demikian, pengabdian ini diharapkan dapat memberikan dampak positif bagi kesehatan remaja putri dan mengurangi risiko anemia pada kelompok ini